The role of waist-to-hip ratio for predicting nonalcoholic fatty liver disease among Korean pediatric patients - Choi, You Jin; Kwon , Yoowon; Choi, So Yoon; Lee, Yoo Min; Yoo, In Hyuk; Kim , Tae Hyeong; Jeong, Sujin (Acta Biomedica Atenei Parmensis, 2025)
Background: The incidence of pediatric nonalcoholic fatty liver disease (NAFLD) has been increasing along with the explosive rise in childhood obesity since the COVID-19 pandemic. Auxiliary markers are needed to more easily screen for and detect NAFLD. This study investigated the potential of waist-to-hip ratio (WHR) as an early diagnostic tool in Korean pediatric patients with NAFLD.Methods: This study included 781 children aged 10–19 years who visited the Bundang CHA Pediatric Gastrointestinal Clinic with signs of obesity, weight gain, or elevated liver function test results between January 2022 and December 2023. Anthropometric measurements included height, weight, waist circumference, and hip circumference. Diagnosis of NAFLD was based on alanine aminotransferase levels and liver ultrasonography.Results: Among participants (460 boys and 321 girls; mean age, 11.40 years), 309 (39.6%) were diagnosed with NAFLD. Boys had a higher frequency of NAFLD (51.1% vs. 23.1% in girls). The WHR cutoff values were 0.825 for boys and 0.875 for girls using receiver operating characteristics curves, both of which were significantly associated with NAFLD. More patients with NAFLD had a WHR above the cutoff value than a BMI percentile >95, indicating the potential importance of WHR for assessing NAFLD risk in children and adolescents.Conclusions: Our data suggest that WHR cutoff values may represent more effective indicators than BMI percentile cutoff values for screening the risk of NAFLD in pediatric patients. Further research is warranted to fully understand the significance of these results for the screening and management of NAFLD in pediatric populations.